Evapotranspiration Rates of Turf Bermudagrasses under Nonlimiting Soil Moisture Conditions in Oklahoma. Issue 3 (1st May 2018) - Amgain, Naba R.; Harris, Dustin K.; Thapa, Santanu B.; Martin, Dennis L.; Wu, Yanqi; Moss, Justin Q.
Abstract : Due to limited water availability and increasing water costs, it is essential to identify and utilize turfgrasses with reduced water use rates. The objective of this study was to evaluate the evapotranspiration rates of bermudagrass ( Cynodon spp.) genotypes under nonlimiting soil moisture conditions in the field at Stillwater, OK. Evapotranspiration rates of 10 bermudagrass genotypes were determined using mini‐lysimeters with calcined clay as rooting media. Daily evapotranspiration (ET) rates were measured before dawn by weighing the mini‐lysimeters from August to September in 2013, 2014, and 2015. A significant genotype × year effect was found. Therefore, data were analyzed separately for each year. Within years, the genotype × date effect was significant only in 2014. In 2013, 'TGS_U3', 'TifTuf', and 'Premier' used more water than OKC 1302, OKC 1163, 'Latitude 36', 'Tifway', and OKC 1131. In 2014, TifTuf, 'Celebration', Tifway, and OKC 1302 used more water than Premier, TGS_U3, 'NorthBridge', OKC 1163, and OKC 1131. In 2015, TifTuf, Celebration, and Latitude 36 used more water than Premier, OKC 1302, OKC 1163, OKC 1131, and NorthBridge. TifTuf ranked consistently in the group of genotypes with the highest ET rates, whereas OKC 1131 ranked consistently in the group of genotypes with lowest ET rates in 2013, 2014, and 2015. The differences in ET rates show the potential for breeding programs to develop bermudagrass cultivars with lower ET rates, which may result in reduced overall ET requirements.